2022
DOI: 10.3390/ijms231810970
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, Functions, and Clinical Impact of Presenilin-1 (PSEN1) Gene

Abstract: Presenilin-1 (PSEN1) has been verified as an important causative factor for early onset Alzheimer’s disease (EOAD). PSEN1 is a part of γ-secretase, and in addition to amyloid precursor protein (APP) cleavage, it can also affect other processes, such as Notch signaling, β-cadherin processing, and calcium metabolism. Several motifs and residues have been identified in PSEN1, which may play a significant role in γ-secretase mechanisms, such as the WNF, GxGD, and PALP motifs. More than 300 mutations have been desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 303 publications
0
31
0
Order By: Relevance
“…In this way, it would be the loss of mechanical homeostasis and the shockwave-like spread of it from the initial foci(s) that would be why AD spreads across the brain. This idea is supported by the existence of AD-causing presenilin mutations that counter-intuitively limit cleavage of APP and hence reduce APP processing (Bagaria et al, 2022; Sun et al, 2017). However, these mutations still give rise to AD, fitting with the idea that this is due to defective force feedback signalling, with the result being that they also accelerate mechanical dyshomeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, it would be the loss of mechanical homeostasis and the shockwave-like spread of it from the initial foci(s) that would be why AD spreads across the brain. This idea is supported by the existence of AD-causing presenilin mutations that counter-intuitively limit cleavage of APP and hence reduce APP processing (Bagaria et al, 2022; Sun et al, 2017). However, these mutations still give rise to AD, fitting with the idea that this is due to defective force feedback signalling, with the result being that they also accelerate mechanical dyshomeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Presenolin can regulate APP processing through γ-secretase. Current studies have shown that PSEN1 is mainly associated with Alzheimer’s disease, amyloidosis, cancer-related genes, cardiomyopathy, disease variation, and cognitive disorders [ 45 , 46 ]. PSEN1 is a well-known gene associated with MCI and AD [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it restores Aβ spatial arrangement and cognition in AD, because of the fact that APP plays a significant role in the sequential proteolytic cleavages that result in the generation of Aβ-peptides. Mutations in APP genes such as presenilin-1 and presenilin-2 and APO-ε4 are implicated in the pathology of AD [ 104 ].…”
Section: Types Of Brain Disordersmentioning
confidence: 99%